Developing The Sustainability Model of BMTs: Empirical Approach - Widiyanto bin Mislan Cokrohadisumarto; Yuli Indah Sari; Yulinda Hardiana (Ekonomi Syariah IAIN Kudus, 2020)
Maintaining the sustainability of microfinance institutions such as BMT is a must because this financial institution is badly needed by the community who do not want to be involved with usury practices. Efforts to build sustainability with a variety of approaches, especially from a more Islamic management approach are needed. This study aims to build a model of sustainability in BMT based on growth in the financing, community support, fraud, Islamic human capital, and Islamic leadership. This research was conducted using a quantitative approach (multiple linear regression with stepwise methods) to get the best model by developing moderating variables. The number of samples used was 105 respondents collected from BMT spread across the Semarang and Pekalongan Residency, Central Java, Indonesia. Based on the results of the study, to build BMT sustainability requires financing growth, support from the community, and good Islamic human capital. An interesting finding is that fraud does not affect the sustainability of BMT, this is possible because the fraud that occurs is still in low intensity. Islamic leadership and Islamic human capital are also unable to moderate the influence of fraud on the sustainability of BMT.